A study of ecocriticism on the representations of ecological conditions in Rawa Gambut - Budi Arianto; Suminto A. Sayuti; Anwar Efendi (Studies in English Language and Education, 2021)
This study aims to determine the representation of the ecological crisis found in the Rawa Gambut drama script written by Conie Sema. This qualitative descriptive research used an ecocritical approach. The data are in the form of words, phrases, sentences, and paragraphs that contain information on ecological conditions. Textual analysis was used to examine the data. Data were collected through reading and note-taking techniques with heuristic and hermeneutic reading. The results showed the themes within the drama script as an ecological crisis in Indonesia due to unfriendly environmental development policies. The representation of the ecological crisis are: 1) ideal ecological conditions are maintained if the utilization pattern is wise and responsible, 2) the ecological crisis is closely related to human intervention, 3) humans are the main cause of ecological disasters, 4) there is a disregard for environmental wisdom principles in the use of sustainable living space, 5) the moral message is the importance of awareness to maintain environmental sustainability, and finally, 6) the author offers an ecocentric paradigm to oppose the ideology of anthropocentrism, which is still the dominant perspective in the natural resource management. This study has implications, along with the importance of educational efforts, to raise awareness of environmental sustainability through drama scripts.